Titanium lithium adsorbent and preparation method and application thereof
The titanium lithium adsorbent prepared by wet grinding, calcining and pickling treatment solves the problem of poor adsorption performance of titanium particle adsorbents in the prior art, and achieves higher lithium adsorption capacity and adsorption performance, which is suitable for the lithium extraction process in salt lakes.
Patent Information
- Application Number
- CN202411774220.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-11
AI Technical Summary
The adsorption performance of existing titanium-based particle adsorbents is poor, making it difficult to effectively separate lithium ions from sodium ions and magnesium ions in salt lake brine.
By wet-mixing the titanium source and the lithium source, calcining and pickling treatment, titanium-based lithium adsorbents with higher surfactivity, better adsorption performance and higher purity were prepared. The method includes pickling to remove impurities before granulation and introducing a source of manganese during calcination to improve adsorption performance.
The lithium adsorption capacity and adsorption performance of titanium-based lithium adsorbents are improved, and the selectivity and adsorption capacity of lithium ions are enhanced. The process is simple, the cost is low and the environmental protection is good.
Smart Images

Figure CN119793405A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium extraction by adsorption, and in particular to a titanium-based lithium adsorbent and a preparation method and application thereof. Background Art
[0002] The development of related industries such as energy storage, 3C consumer electronics, and new energy vehicles continues to drive the demand for lithium resources. There are three main forms of lithium resources: salt lake brine lithium mines in closed basins, pegmatite-type hard rock lithium mines, and sedimentary rock-type clay lithium mines. Among them, salt lake brine lithium mines account for 62.6% of the world's total lithium resources and are the most common form of lithium resources. Although lithium extraction from salt lakes has the advantage of relatively low cost, due to its late development, it is far less mature than the ore lithium extraction process. Therefore, the current development and utilization of lithium resources in my country is still relatively low.
[0003] Due to the inferior quality of my country's salt lakes and the huge differences between the conditions of various salt lakes, if we want to vigorously develop lithium extraction from salt lakes, we must make up for the shortcomings through technological innovation. Separating lithium ions from sodium ions and magnesium ions in salt lake brine is the key to lithium extraction technology from salt lakes. Because they have similar ion hydration radius or ion radius, it is difficult to separate them, and there is a relatively high technical threshold.
[0004] The adsorption method is one of the most widely used and most practical processes in the current extraction of lithium from salt lakes. The adsorption method mainly relies on adsorbents with specific adsorption capacity for lithium ions to achieve the separation of lithium ions, and then uses eluents to elute lithium ions to form lithium ion solutions, which are then concentrated and prepared into lithium salts. The adsorption method has a simple process and a high recovery rate. It has greater advantages than other methods from an economic and environmental perspective and is the mainstream development direction in the current market. The key to developing the adsorption method is to make adsorbents with good adsorption selectivity, high recycling rate, relatively low cost, and no pollution to the environment.
[0005] Commonly used adsorbents are titanium-based adsorbents and aluminum-based adsorbents. Among them, titanium-based adsorbents have the advantages of resistance to sulfate ions and alkali, and can separate lithium ions from lithium-sodium in lithium precipitation mother liquor with high sodium carbonate. Chinese invention patent application CN116371373A discloses a method for preparing a titanium-based granular adsorbent with high adsorption stability. Its main preparation process is preparation of precursor-granulation-acid washing. The maximum lithium adsorption capacity of the prepared adsorbent is 15.6 mg / g, and the adsorption performance is poor. Summary of the invention
[0006] The main purpose of the present invention is to provide a titanium-based lithium adsorbent and a preparation method and application thereof, so as to solve the technical problem that the adsorption performance of titanium-based particle adsorbents in the prior art is poor.
[0007] In order to achieve the above object, according to the first aspect of the present invention, a titanium-based lithium adsorbent and a preparation method and application thereof are provided, and the technical scheme is as follows:
[0008] The preparation method of a titanium-based lithium adsorbent comprises the following steps:
[0009] The titanium source and the lithium source are wet-grinded and mixed and then dried to obtain a mixture; wherein the titanium source comprises titanium dioxide; and the lithium source comprises a lithium-containing inorganic substance;
[0010] calcining the mixed material to obtain a precursor;
[0011] The precursor is subjected to acid washing to obtain a powdery titanium-based lithium adsorbent.
[0012] The above-mentioned method for preparing the titanium-based lithium adsorbent has the following advantages:
[0013] First, wet grinding can reduce the agglomeration between raw powders, making the distribution of components in the mixture more uniform, ensuring that the components can better contact and react with each other during the calcination process, and improving the uniformity of the final titanium adsorbent. The wet grinding process can also refine the particles, reduce the particle size of the raw powder, and increase the specific surface area of the mixture, thereby affecting the reaction efficiency and pickling effect in the subsequent calcination process, so that the generated titanium lithium adsorbent has higher surface activity, better adsorption performance and higher purity.
[0014] Among them, pickling before granulation can more effectively and thoroughly remove impurities (such as metal ions, unreacted raw materials, etc.) in the precursor, avoiding impurities being enclosed inside the particles during the granulation process, affecting the quality of the final titanium-based adsorbent. Pickling treatment can refine the particles of the precursor, making its surface more uniform and more active, more suitable for subsequent granulation treatment, and can obtain a more uniform granular adsorbent. Pickling can also remove some water-soluble impurities on the surface of the precursor, which helps to improve the formability during the granulation process and reduce particle adhesion and agglomeration.
[0015] As a further improvement to the preparation method of the above-mentioned titanium-based lithium adsorbent: the mixture also contains a manganese source. Preferably, the manganese source is at least one of manganese carbonate, manganese hydroxide, manganese nitrate, manganese oxide, and manganese acetate; further preferably, when multiple manganese sources are selected, the molar amount of lithium in various manganese sources is equal. Therefore, the manganese element has a strong adsorption capacity, and the addition of manganese can improve the adsorption performance of the titanium-based lithium adsorbent, enhance its selectivity and adsorption capacity for lithium ions; the mixture containing the manganese source can better withstand the high temperature environment during the calcination process and avoid material performance degradation.
[0016] As a further improvement of the preparation method of the above-mentioned titanium-based lithium adsorbent: the lithium source also includes a lithium-containing organic matter. Preferably, the lithium-containing inorganic matter is at least one of lithium hydroxide, lithium carbonate, lithium oxalate, lithium nitrate, and lithium acetate; the lithium-containing organic matter is at least one of lithium ethyl acetate, lithium acetyl methane, lithium pyrrole, lithium acetonitrile, lithium N-methyliminoethyl acetate, lithium thioacetylacetone, 2-lithium pyridine, 2-lithium oxazole, phenyl lithium, 4-lithium benzoic acid, and 2-lithium pyridine; further preferably, when multiple lithium sources are selected, the lithium molar amounts of various lithium sources are equal. First, lithium-containing organic matter can provide the lithium source required for the adsorbent. The use of multiple lithium sources can adjust the reaction activity of the lithium source, ensuring that the lithium source can participate in the reaction to the maximum extent during the calcination process, thereby improving the performance of the titanium-based adsorbent. Secondly, lithium-containing organic matter can reduce the calcination temperature and time. During the high-temperature calcination process, it can decompose and produce gas, making the precursor more loose and porous, thereby improving the porosity and specific surface area. Moreover, lithium-containing organic matter may form a carbon coating during the calcination process, which can prevent the growth and accumulation of lithium titanate particles, thereby ensuring a smaller particle size and a higher specific surface area.
[0017] Setting an equimolar ratio of manganese source and lithium source helps to form a more uniform ion exchange structure during the reaction, making the precipitation reaction between the reactants more uniform to a certain extent, reducing the side reactions that may be caused by excess or deficiency of a certain substance, promoting stable crystal growth, and helping to form an adsorbent with a more compact structure and better surface properties.
[0018] As a further improvement of the preparation method of the above-mentioned titanium lithium adsorbent: an organic solvent is used as a wet grinding dispersant, and the organic solvent is any of ethanol, tetrahydrofuran (THF), dichloromethane (DCM), ethyl acetate (EtOAc), acetone, acetonitrile, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAC), and N-methylpyrrolidone (NMP). Compared with water, organic solvents usually have lower polarity, which can change the adhesion or wettability between particles (mainly titanium dioxide), promote the uniform dispersion of particles, effectively reduce the aggregation and agglomeration between particles, and avoid the expansion or agglomeration of particles that may be caused by aqueous solutions. Organic solvents can better dissolve the lithium source in the raw materials, so that the organic components can be better mixed with the inorganic raw materials during the wet grinding process, and the more fully mixed mixture can be calcined to obtain a more uniform precursor, thereby optimizing the performance of the final titanium lithium adsorbent. In particular, most lithium-containing organics are stored in corresponding organic solvents, and the organic solvents used can also be used as wet grinding dispersants to improve the wet grinding effect.
[0019] As a further improvement to the preparation method of the above-mentioned titanium-based lithium adsorbent: the molar ratio of lithium, titanium and manganese in the mixture is (2-2.1):1:(0.01-0.1).
[0020] As a further improvement of the preparation method of the above-mentioned titanium-based lithium adsorbent: the calcination treatment is calcination at 500-600° C. for 3-5 hours.
[0021] As a further improvement of the preparation method of the above titanium-based lithium adsorbent: the acid washing treatment is to use a hydrochloric acid solution with a concentration of 0.03 to 0.3 mol / L to wash until the pH of the washing solution is constant at 2 to 3.
[0022] As a further improvement of the preparation method of the above-mentioned titanium-based lithium adsorbent: it also includes granulating the powdered titanium-based lithium adsorbent to obtain a granular titanium-based lithium adsorbent.
[0023] As a further improvement of the preparation method of the titanium-based lithium adsorbent, the granulation process comprises the following steps:
[0024] Dissolving a binder in a granulation solvent, wherein the granulation solvent is any one of DMF, DMAC, and NMP, and the binder includes cellulose acetate and polyethersulfone;
[0025] Stir at 60-70°C for 8-12 hours;
[0026] Adding at least one of polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone and a powdered titanium-based lithium adsorbent to form a mixed slurry;
[0027] The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
[0028] In the above-mentioned granulation process, cellulose acetate is used as a binder, which has good solubility, biodegradability, mechanical properties, plasticity and chemical stability, and polyethersulfone is used as a binder, which has good high temperature stability, mechanical properties, biocompatibility and water permeability. The two binders work synergistically to significantly improve the granulation efficiency and particle quality. Polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone all have good solubility, ductility, flexibility, biocompatibility and hydrophilicity. When used as hydrophilic agents and pore-forming agents, a granular titanium-based lithium adsorbent with uniform pores can be obtained. Preferably, 8 to 12 g of binder and 30 to 50 g of titanium-based lithium adsorbent are added to every 100 mL of granulation solvent.
[0029] In order to achieve the above object, according to the second aspect of the present invention, a titanium-based lithium adsorbent is provided, and the technical scheme is as follows:
[0030] The titanium-based lithium adsorbent is prepared by the preparation method described in the first aspect above.
[0031] In order to achieve the above object, according to the third aspect of the present invention, a lithium extraction method is provided, and the technical scheme is as follows:
[0032] The lithium extraction method adopts the titanium-based lithium adsorbent prepared by the preparation method described in the first aspect to adsorb lithium ions in a lithium-containing solution.
[0033] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:
[0035] Figure 1 The XRD patterns of the precursors of Example 1 and Example 4 and the powdered titanium-based lithium adsorbent are shown in FIG.
[0036] Figure 2 The XRD patterns of the precursors of Examples 1-7 are shown in FIG.
[0037] Figure 3 The XRD patterns of the precursors of Examples 1 and 8-9 are shown in FIG.
[0038] Figure 4 This is the SEM photo of the precursor of Example 1.
[0039] Figure 5 This is the SEM photograph of the precursor of Example 9.
[0040] Figure 6 This is a cross-sectional SEM photograph of the granular titanium-based lithium adsorbent of Example 1.
[0041] Figure 7 This is a surface SEM photograph of the granular titanium-based lithium adsorbent of Example 1. DETAILED DESCRIPTION
[0042] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0043] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0044] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0045] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0046] Example 1
[0047] The preparation method of the titanium-based lithium adsorbent of this embodiment comprises the following steps:
[0048] (1) wet-grinding and mixing a titanium source and a lithium source, and then drying the mixture to obtain a mixed material;
[0049] Among them, the titanium source is amorphous titanium dioxide; the lithium-containing inorganic material includes lithium nitrate and lithium carbonate with equal molar amounts of lithium; the molar ratio of lithium to titanium in the mixture is 2:1; 20 mL of ethanol is added to every 100 g of the mixture as a wet grinding dispersant, and after wet grinding for 2 hours, the mixture is dried at 80°C to obtain a mixture.
[0050] (2) The mixture was calcined at 500° C. for 5 hours to obtain a precursor.
[0051] (3) The precursor is first washed with pure water, and then washed with a hydrochloric acid solution with a concentration of 0.2 mol / L until the pH of the washing solution is constant at 2 to 3, thereby obtaining a powdery titanium-based lithium adsorbent.
[0052] (4) Granulating the powdered titanium-based lithium adsorbent, comprising the steps of:
[0053] Dissolve 10 g of an adhesive in 100 mL of a granulation solvent, wherein the granulation solvent is any of DMF, DMAC, and NMP, and the adhesive comprises cellulose acetate and polyethersulfone in a mass ratio of 4:1;
[0054] Stir at 65°C for 10 hours;
[0055] Add 1 mL of polyethylene oxide and 40 g of powdered titanium-based lithium adsorbent to form a mixed slurry;
[0056] The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
[0057] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 15.8 mg / g.
[0058] Example 2
[0059] The preparation method of the titanium-based lithium adsorbent of this embodiment comprises the following steps:
[0060] (1) wet-grinding and mixing a titanium source and a lithium source, and then drying the mixture to obtain a mixed material;
[0061] Among them, the titanium source is amorphous titanium dioxide; the lithium-containing inorganic material includes lithium nitrate, lithium carbonate and lithium acetate with equal molar amounts of lithium; the molar ratio of lithium to titanium in the mixture is 2.05:1; 20 mL of ethanol is added to every 100 g of the mixture as a wet grinding dispersant, and after wet grinding for 2 hours, the mixture is dried at 80°C to obtain a mixture.
[0062] (2) The mixture was calcined at 550° C. for 4 hours to obtain a precursor.
[0063] (3) The precursor is first washed with pure water, and then washed with a hydrochloric acid solution with a concentration of 0.2 mol / L until the pH of the washing solution is constant at 2 to 3, thereby obtaining a powdery titanium-based lithium adsorbent.
[0064] (4) Granulating the powdered titanium-based lithium adsorbent, comprising the steps of:
[0065] Dissolve 10 g of an adhesive in 100 mL of a granulation solvent, wherein the granulation solvent is any of DMF, DMAC, and NMP, and the adhesive comprises cellulose acetate and polyethersulfone in a mass ratio of 1:1;
[0066] Stir at 65°C for 10 hours;
[0067] Add 0.5 mL of polyvinyl alcohol and 40 g of powdered titanium-based lithium adsorbent to form a mixed slurry;
[0068] The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
[0069] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 16.3 mg / g.
[0070] Example 3
[0071] The preparation method of the titanium-based lithium adsorbent of this embodiment comprises the following steps:
[0072] (1) wet-grinding and mixing a titanium source and a lithium source, and then drying the mixture to obtain a mixed material;
[0073] Among them, the titanium source is amorphous titanium dioxide; the lithium-containing inorganic material includes lithium nitrate, lithium carbonate, lithium acetate and lithium oxalate with equal lithium molar amounts; the molar ratio of lithium to titanium in the mixture is 2.05:1; 20 mL of ethanol is added to every 100 g of the mixture as a wet grinding dispersant, and after wet grinding for 2 hours, the mixture is dried at 80°C to obtain a mixture.
[0074] (2) The mixture was calcined at 550° C. for 4 hours to obtain a precursor.
[0075] (3) The precursor is first washed with pure water, and then washed with a hydrochloric acid solution with a concentration of 0.2 mol / L until the pH of the washing solution is constant at 2 to 3, thereby obtaining a powdery titanium-based lithium adsorbent.
[0076] (4) Granulating the powdered titanium-based lithium adsorbent, comprising the steps of:
[0077] Dissolve 10 g of an adhesive in 100 mL of a granulation solvent, wherein the granulation solvent is any of DMF, DMAC, and NMP, and the adhesive comprises cellulose acetate and polyethersulfone in a mass ratio of 2:3;
[0078] Stir at 65°C for 10 hours;
[0079] Add 2 g of polyvinyl pyrrolidone and 40 g of powdered titanium-based lithium adsorbent to form a mixed slurry;
[0080] The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
[0081] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 16.6 mg / g.
[0082] Example 4
[0083] The preparation method of the titanium-based lithium adsorbent of this embodiment comprises the following steps:
[0084] (1) wet-grinding and mixing a titanium source and a lithium source, and then drying the mixture to obtain a mixed material;
[0085] Among them, the titanium source is amorphous titanium dioxide; the lithium-containing inorganic material includes lithium nitrate, lithium carbonate, lithium acetate, lithium oxalate and lithium hydroxide with equal lithium molar amounts; the molar ratio of lithium to titanium in the mixture is 2.1:1; 20 mL of ethanol is added to every 100 g of the mixture as a wet grinding dispersant, and after wet grinding for 2 hours, the mixture is dried at 80°C to obtain a mixture.
[0086] (2) The mixture was calcined at 600° C. for 3 hours to obtain a precursor.
[0087] (3) The precursor is first washed with pure water, and then washed with a hydrochloric acid solution with a concentration of 0.2 mol / L until the pH of the washing solution is constant at 2 to 3, thereby obtaining a powdery titanium-based lithium adsorbent.
[0088] (4) Granulating the powdered titanium-based lithium adsorbent, comprising the steps of:
[0089] Dissolve 10 g of an adhesive in 100 mL of a granulation solvent, wherein the granulation solvent is any of DMF, DMAC, and NMP, and the adhesive comprises cellulose acetate and polyethersulfone in a mass ratio of 1:4;
[0090] Stir at 65°C for 10 hours;
[0091] Add 1 mL of polyethylene oxide and 40 g of powdered titanium-based lithium adsorbent to form a mixed slurry;
[0092] The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
[0093] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 16.9 mg / g.
[0094] Example 5
[0095] Compared with Example 1, the preparation method of the titanium-based lithium adsorbent of this embodiment has the following differences: the lithium source also includes a lithium-containing organic matter, and the lithium-containing organic matter is ethyl lithium acetate; and the lithium molar amounts of various lithium sources are equal.
[0096] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 16.7 mg / g.
[0097] Example 6
[0098] Compared with Example 2, the preparation method of the titanium-based lithium adsorbent of this embodiment has the following differences: the lithium source also includes lithium-containing organic matter, and the lithium-containing organic matter is lithium ethyl acetate and lithium acetyl methane; the lithium molar amounts of various lithium sources are equal.
[0099] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 17.1 mg / g.
[0100] Example 7
[0101] Compared with Example 3, the preparation method of the titanium-based lithium adsorbent of this embodiment has the following differences: the lithium source also includes lithium-containing organic matter, and the lithium-containing organic matter is 4-lithium benzoic acid, 2-lithium pyridine and lithium thioacetylacetone; the lithium molar amount of various lithium sources is equal.
[0102] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 17.3 mg / g.
[0103] Example 8
[0104] Compared with Example 1, the preparation method of the titanium-based lithium adsorbent of this embodiment is different in that the mixture further contains a manganese source, which is manganese carbonate, and the molar ratio of titanium to manganese is 1:0.01.
[0105] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 16.4 mg / g.
[0106] Example 9
[0107] Compared with Example 6, the preparation method of the titanium-based lithium adsorbent of this embodiment is different in that the mixture also contains a manganese source, which is manganese carbonate, manganese hydroxide and manganese nitrate with equal manganese molar ratios, and the molar ratio of titanium to manganese is 1:0.1.
[0108] According to the test, the lithium adsorption capacity of the titanium-based lithium adsorbent of this embodiment is 18.2 mg / g.
[0109] Figure 1 The XRD patterns of the precursors and powdered titanium-based lithium adsorbents of Examples 1 and 4 are shown in FIG. Figure 1 As shown, the XRD pattern of the precursor corresponds to the Li 2 TiO 3 The structure is consistent. After acid washing, the hydrogen ions successfully replaced the lithium ions in the precursor to form a new crystal form.
[0110] Figure 2 The XRD patterns of the precursors of Examples 1-7 are shown in FIG. Figure 2 As shown, the precursors prepared under different lithium sources and process parameters have the same crystal form.
[0111] Figure 3 The XRD patterns of the precursors of Examples 1 and 8-9 are shown in Table 1. Figure 3 As shown in the figure, the introduction of manganese did not change the crystal form of the precursor, and the precursors before and after doping formed Li 2 TiO 3 structure.
[0112] Figure 4 This is the SEM photo of the precursor of Example 1. Figure 5 This is a SEM photo of the precursor of Example 9. Figure 4-5 As shown, the particles of manganese-doped precursor are smaller, with a higher specific surface area, and are more easily involved in lithium adsorption reaction.
[0113] Figure 6 This is a cross-sectional SEM photograph of the granular titanium-based lithium adsorbent of Example 1. Figure 7 This is a surface SEM photograph of the granular titanium-based lithium adsorbent of Example 1. Figure 6-7 As shown, the surface and cross-section of the granular titanium-based lithium adsorbent have sufficient mesh structure, which can provide more lithium adsorption sites and promote the adsorption of lithium.
[0114] The granular titanium-based lithium adsorbent of Example 1 was tested for recycling use and found that the lithium adsorption capacity of the 20th use was still as high as 15.2 mg / g, showing excellent lithium adsorption stability.
[0115] The above-mentioned test method for lithium adsorption capacity is as follows: 0.5g of titanium-based lithium adsorbent is dried to constant weight and then added to 50mL of lithium precipitation mother liquor (pH is 10, lithium ion concentration is 1359mg / L, sodium ion concentration is 118730mg / L); then, the mixed solution is placed in a constant temperature water bath oscillator and oscillated for 1h to adsorb lithium; then, the titanium-based lithium adsorbent is separated by filtration; then, the titanium-based lithium adsorbent is added to 100mL, 0.2mol / L hydrochloric acid solution and oscillated in a constant temperature water bath for 1h for acid washing and desorption.
[0116] Lithium adsorption capacity Q e The calculation formula for (mg / g) is: Among them, C 0 is the concentration of lithium ions in the desorption solution (mg / L), V is the volume of the desorption solution (L), and m is the mass of the titanium-based lithium adsorbent (g).
[0117] Among them, lithium precipitation mother liquor refers to the liquid after sodium carbonate is added to lithium-rich liquid to generate lithium carbonate precipitation and filtered. Its main components are a large amount of carbonate, sodium ions and residual lithium ions, which is an alkaline environment suitable for titanium-based adsorbents to adsorb and extract lithium; lithium precipitation mother liquor is commonly found in the lithium carbonate production process of lithium mines and the lithium extraction process of salt lakes. Lithium carbonate can be obtained after the desorption liquid is concentrated, impurity-removed, crystallized, and lithium is extracted, realizing the deep recovery of lithium carbonate.
[0118] The lithium-sodium ratio of the lithium precipitation mother liquor is 0.0114. The lithium-sodium ratios of the desorption liquid after the granular titanium-based lithium adsorbent of Examples 1-4 adsorbed the lithium precipitation mother liquor were 21.7, 34.8, 46.8 and 64.9, respectively. Compared with the lithium-sodium ratio of 0.0114 of the lithium precipitation mother liquor, the lithium was concentrated thousands of times, indicating that the titanium-based lithium adsorbent of the present invention has a good selective adsorption effect in the lithium precipitation mother liquor; at the same time, the concentration of titanium ions in the desorption liquid is less than or equal to 0.01, and the dissolution loss of titanium is extremely low.
[0119] The pH of the lithium precipitation mother solution was further adjusted to 8.5, and the lithium-sodium ratios of the desorption solutions of Examples 1-4 were 12.3, 15.9, 11.6 and 17.5, respectively. It can be seen that the titanium-based lithium adsorbent of the present invention has good alkali resistance and good selectivity for lithium.
[0120] In addition to the above-mentioned lithium precipitation mother liquor, the titanium-based lithium adsorbent of the present invention can also be used for adsorption and extraction of lithium from other alkaline lithium-rich liquors.
[0121] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing a titanium-based lithium adsorbent, characterized in that: The following steps are involved: The titanium source and the lithium source are wet-grinded and mixed and then dried to obtain a mixture; wherein the titanium source comprises titanium dioxide; and the lithium source comprises a lithium-containing inorganic substance; calcining the mixed material to obtain a precursor; The precursor is subjected to acid washing to obtain a powdery titanium-based lithium adsorbent.
2. The method for preparing a titanium-based lithium adsorbent according to claim 1, characterized in that: The mixed material further contains a manganese source; and / or the lithium source further contains lithium-containing organic matter.
3. The method for preparing a titanium-based lithium adsorbent according to claim 2, wherein: The manganese source is at least one of manganese carbonate, manganese hydroxide, manganese nitrate, manganese oxide, and manganese acetate; The lithium-containing inorganic substance is at least one of lithium hydroxide, lithium carbonate, lithium oxalate, lithium nitrate, and lithium acetate; The lithium-containing organic matter is at least one of lithium ethyl acetate, lithium acetyl methane, lithium pyrrole, lithium acetonitrile, lithium N-methyliminoethyl acetate, lithium thioacetylacetone, 2-lithium pyridine, 2-lithium oxazole, phenyl lithium, 4-lithium benzoic acid, and 2-lithium pyridine; Organic solvents are used as wet grinding dispersants.
4. The method for preparing a titanium-based lithium adsorbent according to claim 3, characterized in that: The molar ratio of lithium, titanium and manganese in the mixture is (2-2.1):1:(0.01-0.1); when multiple lithium sources are selected, the molar amounts of lithium in the various lithium sources are equal; when multiple manganese sources are selected, the molar amounts of lithium in the various manganese sources are equal; the organic solvent is any one of ethanol, tetrahydrofuran, dichloromethane, ethyl acetate, acetone, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone.
5. The method for preparing a titanium-based lithium adsorbent according to claim 1, wherein: The calcination treatment is performed at 500-600° C. for 3-5 hours.
6. The method for preparing a titanium-based lithium adsorbent according to claim 1, wherein: The acid washing treatment is to use a hydrochloric acid solution with a concentration of 0.03-0.3 mol / L to wash until the pH of the washing solution is constant at 2-3.
7. The method for preparing a titanium-based lithium adsorbent according to claim 1, wherein: The method also includes granulating the powdered titanium-based lithium adsorbent to obtain a granular titanium-based lithium adsorbent.
8. The method for preparing a titanium-based lithium adsorbent according to claim 7, characterized in that: The granulation process includes the steps: Dissolving a binder in a granulation solvent, wherein the granulation solvent is any one of DMF, DMAC, and NMP, and the binder includes cellulose acetate and polyethersulfone; Stir at 60-70°C for 8-12 hours; Adding at least one of polyethylene oxide, polyvinyl alcohol, and polyvinyl pyrrolidone and a powdered titanium-based lithium adsorbent to form a mixed slurry; The mixed slurry is added dropwise into pure water to obtain a granular titanium-based lithium adsorbent.
9. Titanium-based lithium adsorbent, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium extraction method, characterized in that: The titanium-based lithium adsorbent prepared by the preparation method described in any one of claims 1 to 8 adsorbs lithium ions in a lithium-containing solution.
Citation Information
Patent Citations
Preparation method of titanium particle adsorbent with high adsorption stability
CN116371373A